Implementation of terminal middleware platform for mobile RFID computing. (11th November 2011) - Park, Namje
The typical Radio Frequency Identification (RFID) architecture, defined by EPCglobal, comprises RFID tags, which are embedded or attached to objects, an RFID reader and Information Services (ISs) server. The RFID reader can be stationary or mobile; the latter enables more applications. This paper describes the core components required for realising a mobile RFID application, such as mobile RFID reader and the platform and network architectures. Although several types of mobile RFID readers are available, we propose and analyse the characteristics of customised mobile RFID technology, which affords several advantages related to security, network architecture, and operation scenario etc.